Preserving Fertility in Children and Adolescents with Cancer - Jennifer M. Levine (MDPI AG, 2014)
In the face of excellent survival rates for pediatric and adolescent cancer, preserving the opportunity to have biological children is an important component of long term quality of life. Yet, modern chemotherapeutic regimens continue to pose a threat to fertility. The only fertility preservation methods available to pre-pubertal children of both genders is cryopreservation of gonadal tissue, a highly experimental intervention, or shielding/re-location of reproductive tissue in the setting of radiation. These techniques are available in the post pubertal population as well, but post pubertal patients also have the option for cryopreservation of gametes, a process that is much simpler in males than females. For this reason, prior to the initiation of therapy, sperm banking should be considered standard of care for males, while consideration of embryo or oocyte cryopreservation should be limited to those females at risk of developing ovarian failure. Attention to reproductive health and fertility preservation should continue after the completion of therapy. Establishing programs that streamline access to current fertility preservation techniques will assist in ensuring that all eligible patients can avail themselves of current options.